Development of oncological diseases after organ transplantation - A. V. Babkina; M. Sh. Khubutiya (Трансплантология (Москва), 2022)
With the increase in the population of patients with transplanted organs, the risk of developing oncological diseases has become proportionally high, which may be the cause of poor quality of life, and also of a high mortality among the patients with transplanted organs. The review examines the risk factors, incidence, and the impact of malignant neoplasms on the survival in patients with transplanted organs. The rapid development of clinical transplantology, the use of new drugs and immunosuppression regimens poses new challenges for oncologists and transplantologists. The analysis of oncopathology incidence in patients with transplanted organs allows us to conclude about its impact on the long-term life prognosis and the need to include preventive measures in transplantation practice.